Case report: Synchronous tumors of the female reproductive tract in systemic lupus erythematosus: report of two cases and review of the literature - Wang, Ling; Zhang, Qin; Shi, Nan; Wang, Jiaxi; Song, Shuang; Yang, Huadi; Chen, Xingbei (Frontiers in Oncology, 2024)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that affects multiple systems. Patients with SLE are prone to a variety of malignancies, especially neoplasms of the female reproductive tract. Synchronous tumors, considered to involve multiple sites, are rare in the female reproductive tract. There are hardly any reports of SLE with synchronous reproductive tract tumors.We report the occurrence of two to three reproductive tract tumors in two women with SLE. A 52-year-old female was diagnosed with vulvar cancer and cervical cancer.Another female, aged 67, was diagnosed with concurrent vulvar cancer, vaginal cancer, and cervical cancer, and also presented with a suspected lung cancer.The presence of synchronous tumors of the reproductive tract in patients with SLE is uncommon and can be easily disregarded. It is crucial to highlight that SLE patients with multiple primary malignancies exhibit notable late-stage presentation at the time of diagnosis, inadequate disease-free survival, poor overall survival, rapid progression rates, and mortality. Consequently, greater awareness must be generated regarding synchronous reproductive tract tumors in SLE and share frst authorship.